Pelaksanaan Pembinaan dan Pengawasan dalam Rangka Meningkatkan Sinergitas dan Efisiensi Penyelenggaraan Pemerintahan Daerah: (Studi Kasus di Propinsi Kepulauan Bangka Belitung) - Tambun, Eliakim (Jurnal Bina Praja, 2009)
In order for the implementation of regional government to realize efficiency and effectiveness in increasing development and public welfare, as mandated by Law No. 32 of 2004 concerning Regional Government, the government is required to provide guidance and supervision of the implementation of regional government. In reality, so many institutions feel interested in implementing supervision of the implementation of regional government whose effectiveness needs to be known. For this reason, research is needed on the implementation of guidance and supervision in order to increase the synergy and efficiency of the implementation of regional government. The research method used is the survey method to be able to describe the phenomenon and reveal the relationship between variables. The results of the study indicate that a policy is needed to synergize all levels of supervision, the prosecutor's office, the police, the Corruption Eradication Committee, and others that are regulated by laws and regulations.